Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society 2020
DOI: 10.1145/3419249.3420141
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Women Managing Pregnancy Complications in Rural Ecuador

Abstract: Previous research has explored the potential use of digital health to support maternal health in the Global South highlighting the importance of understanding the socio-cultural context to inform system design. However, the experiences of indigenous women managing pregnancy complications in Latin America remain underexplored in HCI. We present a qualitative study with 25 indigenous pregnant women in an Ecuadorian rural community looking at their experiences during complications, their antenatal care visits and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 118 publications
0
12
0
Order By: Relevance
“…In other cases, when the woman's health decisions depended on the husband e.g., family planning methods, delays or refusal by the husband was reported. Machismo and gender stereotypes have been documented as strongly ingrained characteristics of Ecuadorian indigenous culture [21,48]. And it has also been observed that women are more accepting of contraceptive methods than men [49] so empowering women can be the key to avoid unwanted pregnancies [21].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In other cases, when the woman's health decisions depended on the husband e.g., family planning methods, delays or refusal by the husband was reported. Machismo and gender stereotypes have been documented as strongly ingrained characteristics of Ecuadorian indigenous culture [21,48]. And it has also been observed that women are more accepting of contraceptive methods than men [49] so empowering women can be the key to avoid unwanted pregnancies [21].…”
Section: Discussionmentioning
confidence: 99%
“…Machismo and gender stereotypes have been documented as strongly ingrained characteristics of Ecuadorian indigenous culture [21,48]. And it has also been observed that women are more accepting of contraceptive methods than men [49] so empowering women can be the key to avoid unwanted pregnancies [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations